Green culinary innovation in traditional banana processing: A zero waste approach to sustainable food - Sunjaya, Nicholas Ethan; Anindyamayza, Najwa Pinandhita; Hartajanie, Laksmi; Lindayani, Lindayani (Journal of Tourism, Culinary, and Entrepreneurship (JTCE), 2025)
In 2020, national banana production in Indonesia reached 8,182,756 tons, a 12.39% increase compared to 2019. Banana processing into sale pisang is one solution to address the overproduction. This study aims to utilize local banana production, reduce plastic waste, implement the zero-waste concept, and produce sustainable products. The method involves peeling bananas, drying the flesh using a solar tunnel dryer (STD), packaging with eco-friendly materials, and calculating product cost through the Cost of Goods Sold (COGS) approach. The banana peels are reprocessed by adding water and molasses to produce eco-enzymes, which function as liquid fertilizer. The outcomes are two sustainable products: sale pisang and eco-enzymes. Sale pisang has strong potential as a business opportunity to support the growth of micro, small, and medium enterprises (MSMEs) in Indonesia. The use of the STD enhances hygiene and food safety compared to traditional open sun drying by providing controlled temperature and airflow. To support sustainability, applying green technology and zero-waste principles is essential, as it maximizes the utilization of all banana components. In conclusion, this research demonstrates how local banana production can be converted into value-added, eco-friendly products that support sustainable development goals.